Translation and validation of the German version of the FACE-Q paralysis module in adult patients with unilateral peripheral facial palsy - Wieta Elin Moritz; Gerd Fabian Volk; Helene Kreysa; Orlando Guntinas-Lichius (Scientific Reports, 2024)
Abstract The aim was to develop and validate a German version of the FACE-Q paralysis module, a patient-reported outcome measure to assess health-related quality of life in adult patients with unilateral facial palsy. The FACE-Q craniofacial questionnaire, which includes the paralysis module, was translated. 213 patients with facial palsy completed the German FACE-Q paralysis along with the established FDI and FaCE questionnaires. Regression analyses were performed to examine the relationships between the different FACE-Q domains and patient and therapy characteristics. The FACE-Q scales had high internal consistency (Cronbach’s alpha all > 0.6). High correlations were found between the FACE-Q and the FDI and FaCE (mean rho = 0.5), as well as within the FACE-Q (mean rho = 0.522). Unifactorial influences were found for all domains except Breathing (all p < 0.05). Multivariate independent predictors were found for some FACE-Q domains. Most influential predictors (> 8 subdomains): Patients who received physical therapy scored lower in ten subdomains than those who did not (all p < 0.05). Patients who had surgery scored lower in nine subdomains than patients without surgery (all p < 0.05). The German version of the FACE-Q Paralysis Module can now be used as a patient-reported outcome instrument in adult patients with facial nerve palsy.